Effectiveness of Implementing PBL-SSI-Based Electronic Modules on Reflective Judgment and Communication Skills of Muhammadiyah High School Students - Mahendra, Reno Esa; Sumah, Astrid Sri Wahyuni; Genisa, Marlina Ummas (BIOEDUSCIENCE, 2024)
Background: The PBL-SSI model approach can develop students' reflective judgment and communication skills at school because learning with this model is based on scientific concepts that impact people's lives. This research aims to determine the effectiveness of implementing SSI-based electronic modules in improving the reflective judgment and communication skills of class X Muhammadiyah High School students in Palembang City. Methods: The research method uses a quantitative descriptive method, with the research subjects being biology teachers and class X students at SMA Muhammadiyah 1 and SMA Muhammadiyah 5, Palembang City. This research is quasi-experimental, with a pretest-posttest non-equivalent control group design. Results: The research results show that the effectiveness value of the PBL-SSI electronic module can increase reflective judgment, as seen from the N-gain value results. Muhammadiyah 1 High School in the control class has 40% less effective criteria, and the experimental class has 71% sufficient criteria that are effective. Muhammadiyah High School 5 in the control class was 25% ineffective criteria, and the experimental class was 61% quite effective criteria. Meanwhile, the results of communication skills were obtained by SMA Muhammadiyah 1 in the control class with a score of 76 good criteria, the experimental class with a score of 83 perfect criteria, SMA Muhammadiyah 5 in the control class with a score of 79 good criteria, the experimental class with a score of 88 perfect criteria. Conclusions: Applying PBL-SSI-based electronic modules on environmental change material effectively improves students' reflective judgment and communication skills.